PERCEPATAN PEMBANGUNAN DAERAH MELALUI MANAJEMEN PEMBANGUNAN INFRASTRUKTUR DI KECAMATAN LONG BAGUN KABUPATEN MAHAKAM ULU - Evolonia Dypuri Dew (Jurnal Paradigma (JP), 2017)
This study aims to describe and analyze the management of infrastructure development in the roads and bridges sector, analyzing and describing the impacts and benefits of infrastructure development on the society, as well as describing and analyzing the factors that hamper and support the management of infrastructure development, especially in roads and bridges in Long Bagun Sub-district Mahakam Ulu Regency. This study uses a qualitative approach and the data obtained by interview technique, observation, and documentation, which then is described with qualitative approach by using data analysis through data condensation stage, data presentation, and conclusion / verification. Based on the research results, can be concluded that the management of infrastructure development in Long Bagun Sub-district Mahakam Ulu District reviewed from Planning, Organizing / Implementation and Supervision of infrastructure development in the field of road and bridge infrastructure has been running quite well, although in the implementation of infrastructure development in the field of road and bridge infrastructure which runs less satisfactory results for the society.Keywords: management, infrastructur, development